2D atomic crystal molecular superlattices by soft plasma intercalation - Lufang Zhang (Nature Portfolio, 2020)
Two-dimensional (2D) atomic crystal superlattices offer technological opportunities beyond the reach of existing materials. Here, the authors produce 2D atomic crystal molecular superlattices by intercalating O2 molecules into the interlayer space of 2D materials using a soft plasma strategy.